Ritual and language - Kádár, Dániel Z. (Cambridge University Press, 2024)
"Illustrated with numerous in-depth case studies, this pioneering book provides a cutting-edge introduction to ritual language use, a fundamental aspect of communication in everyday life. Offering a new framework for the pragmatic study of ritual, it is essential reading for both researchers and students in pragmatics and applied linguistics"--